Northeast Migrants in Delhi Race, Refuge and Retail - McDuie-Ra, Duncan (Amsterdam University Press, 2012)
Northeast Migrants in Delhi: Race, Refuge and Retail is an ethnographic study of migrants from India's north-east border region living and working in Delhi, the nation's capital. Northeast India borders China, the Himalayas, and Southeast Asia. Despite burgeoning interest in the region, little attention is given to the thousands of migrants leaving the region for Indian cities for refuge, work, and study. The stories of Northeast migrants reveal an everyday Northeast India rarely captured elsewhere and offer an alternative view of contemporary India. Northeast migrants covet the employment opportunities created by India's embrace of globalization; shopping malls, restaurants, and call centres. Yet Northeast migrants also experience high levels of racism, harassment, and violence. Far from simply victims of the city, Northeast migrants have created their own 'map' of Delhi, enabling a sense of belonging, albeit an uneasy one. Interdisciplinary in nature, this book will appeal to scholars of anthropology, urban studies, geography, migration, and Asian Studies.